Identifying interrelationships among factors affecting innovation archetypes: the case of China. Issue 4 (25th November 2020) - Al-Sayed, Rafif; Yang, Jianhua
Abstract : Purpose: This paper aims at studying the concept of innovation ecosystems and investigating the factors affecting them based on their interrelationships with respect to different innovation archetypes. Design/methodology/approach: The methodology is based on using multivariate statistical analysis of the inter-correlations among a number of variables which led to extracting a reduced set of new significant factors that affect China's innovation ecosystem. Findings: The results showed that innovation archetypes differ significantly with respect to the majority of the new factors. Practical implications: Through identifying these challenges, decision-makers can develop a better understanding of the variables affecting each archetype of innovation and act accordingly. Originality/value: The study is the first to fill the gap of addressing a large number of variables affecting innovation and analyzing their interrelationships.